Lipid Profile in Type 2-Diabetic Women with Central Obesity and Non-central Obesity - Nurvitasari, Scholastica Diana; Natalia MS, Nanny; Yoanita, Yovi (Althea Medical Journal, 2016)
Background: Type 2 Diabetes Mellitus and central obesity are associated with higher risk of cardiovascular diseases especially in women. Lipid profile may reflect dyslipidemia which includes hypertriglyceridemia, increased level of LDL-C, total cholesterol, and reduced HDL-C level in the blood. Patients with central obesity tend to have dyslipidemia compared to those without central obesity counterpart. The study aimed at comparing lipid profile in central-obese diabetic women and nonâcentral-obese diabetic women. Methods: This study was an analytical study with crossâsectional approach conducted in Dr. Hasan Sadikin General Hospital, Bandung, Indonesia in 2013. A total of 160 data contained of waist circumference (WC) and the level of total cholesterol, triglyceride, HDL-C and LDL-C were obtained from medical record of Diabetic patients within the period of January 2010âJanuary 2012. Women patients whose WC of â¥80 cm were classified as central obesity while WC of <80 cm were classified as non-central obesity. The t-test was used to compare means of different variables, p<0.05 was considered as statistically significant.Results: Central obese diabetic women when compared to non-central obese diabetic women showed statistically significant increase in the level of total cholesterol serum, triglyceride serum and decrease in HDL-C serum level (p<0.05). The LDL-C serum level did not show statistical significant difference in the two groups (p>0.05).Conclusions: Diabetic patients with central obesity tend to have higher level of total cholesterol and triglyceride and lower level of HDL-C compared to diabetic patients without central obesity. [AMJ.2016;3(4):570â6]Â DOI:Â 10.15850/amj.v3n4.941